2020
DOI: 10.1126/sciadv.abb8227
|View full text |Cite
|
Sign up to set email alerts
|

Cenozoic evolution of the steppe-desert biome in Central Asia

Abstract: The origins and development of the arid and highly seasonal steppe-desert biome in Central Asia, the largest of its kind in the world, remain largely unconstrained by existing records. It is unclear how Cenozoic climatic, geological, and biological forces, acting at diverse spatial and temporal scales, shaped Central Asian ecosystems through time. Our synthesis shows that the Central Asian steppe-desert has existed since at least Eocene times but experienced no less than two regime shifts, one at the Eocene–Ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
59
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 146 publications
10
59
0
Order By: Relevance
“…This shift is again coeval with the onset of obliquity cycles (Bosboom et al, 2014) as well as the appearance of the loess-like end-member observed in our grain-size analyses ( Figure 6). The late Eocene record is characterized by the appearance of conifers at ∼37 Ma, as recognized in previous studies, and linked to cooling and aridification (Abels et al, 2011;Barbolini et al, 2020;Dupont-Nivet, Hoorn, & Konert, 2008;Page et al, 2019).…”
Section: Palynologysupporting
confidence: 66%
See 1 more Smart Citation
“…This shift is again coeval with the onset of obliquity cycles (Bosboom et al, 2014) as well as the appearance of the loess-like end-member observed in our grain-size analyses ( Figure 6). The late Eocene record is characterized by the appearance of conifers at ∼37 Ma, as recognized in previous studies, and linked to cooling and aridification (Abels et al, 2011;Barbolini et al, 2020;Dupont-Nivet, Hoorn, & Konert, 2008;Page et al, 2019).…”
Section: Palynologysupporting
confidence: 66%
“…Composite of the early late Eocene record of the Xining Basin based on magnetostratigraphic correlations between the studied sections. The composite shows the lithostratigraphy, cyclostratigraphy and end-member abundances of the grain-size record and Plant Functional Type abundances of the palynological record with new samples from this study and Barbolini et al (2020) indicated in red. The magnetostratigraphy is correlated to the GTS16 (Ogg et al, 2016).…”
Section: Cyclostratigraphymentioning
confidence: 99%
“…In the northern hemisphere, Eurasia was dominated by subtropical evergreen and mixed mesophytic forests with many thermophilic elements, while most conifers were generally restricted to sites at elevation (Akgün et al, 2007;Ivanov et al, 2011;Kovar-Eder et al, 2008;Utescher et al, 2011;Yao et al, 2011), while Turkey was dominated by laurel forest and subordinate broadleaf deciduous forest biomes (Denk et al, 2019). In contrast, an arid belt stretched across Central Asia (Caves et al, 2016;Sun & Wang, 2005) that impeded vegetation growth in desert intermontane basins, with semiarid woodlands on slopes and in river valleys, and conifer forests at higher elevations (Barbolini et al, 2020). Evidence from fossil phytoliths and time-calibrated molecular phylogenies suggest that open-habitat grasses (including C3 pooids, PACMAD grasses, and C4 chloridoids) radiated taxonomically well before the Miocene (Christin et al, 2014;Strömberg, 2011).…”
Section: Early Miocene (Aquitanian and Burdigalian) Vegetationmentioning
confidence: 99%
“…All rights reserved. mixed coniferous broadleaved forests, mesophytic forests, and herbaceous floras in lakeside/riverine associations, as well as steppes and C3/C4-dominated grasslands (Denk et al, 2018;Strömberg, 2011;Barbolini et al, 2020) (Fig. 4).…”
Section: Accepted Articlementioning
confidence: 99%
“…These climatic changes likely restructured the habitats for species (e.g. the desert‐to‐steppe biome change in Central Asia; Barbolini et al., 2020) and thus, facilitated the dispersal events into the TP from surrounding regions (Ding et al., 2020; Pisano et al., 2015). Furthermore, we recorded a sharp increase in dispersal events from the late Miocene ( c .…”
Section: Discussionmentioning
confidence: 99%